Cognitive Process By Students’ Majoring in Natural and Social Science in Writing Analytical Exposition Text - Rinda Sari Putri; Anni Holila Pulungan; Rahmad . Husein (Universitas Negeri Medan, 2021)
This study deals with the cognitive process by students’ majoring in natural and social science in Writing Analytical Exposition Text. This study attempted to investigate the reasons why the cognitive process happens in writing analytical exposition text the way it does. The data in this study were the students of SMA Nurul Iman from two different majors; they were three students of Natural Science Major and three students of Social Science Major. This study was conducted by using qualitative design of which instrument are both writing test and interview. The research findings show that the cognitive processes of the students of the two majors were different in planning, translating and reviewing. The students majoring in natural and social science write analytical exposition in similarity and different cognitive process. The similarity is that both students majoring write analytical text in terms three stages; planning, translating, and reviewing, and the different are that the two major student perform cognitive process in different stage. The students majoring in Natural Science use the information in the assignment to generate new information then relate it with their experience and they know about the topic to be developed. Whereas, students majoring in Social Science do not really know about the topic and do not relate it with their experience so that way they could not generate content information and develop the text. Keywords: Cognitive Process, Analytical, Different Major, Social Science, Natural Sciences